Christianisme Orthodoxe et Nationalisme: Deux composantes de la culture politique grecque moderne - Lipowatz, Thanos (Études helléniques / Hellenic Studies, 1998)
Orthodox Christianity and communalistic nationalism – used together in the imperial and ecclesiastical hierarchies since the beginning of the Byzantine Empire (Hierocracy) and continued in the fusion of Church and Nation within the Church hierarchy (Ethnarchy) during the Ottoman Empire – have had a lasting influence on the ‘political culture’ end the ‘process of civilization’ and have fostered the ‘atrophy of the civic society’. The absence of the notions of ‘natural law’ and ‘human rights’ in the Greek world, notions which have been present in Western Europe since the Middle Ages, perpetuates the personification of institutions and authority in the spirit of the Greek people and inhibits, the modernization of contemporary Greek society. At this historical point, Greek society, with its ‘traditional communal individualism, faces with suspicion the Western mentality with its voluntaristic and legalistic individualism.